PENGARUH STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL KONTROL - Effendi, Elwan; Sri Hasnawati (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
This investigation is seek to investigate how capital structur and dividend policy effect stock pricees, with profitability, messured through return on asets, acting as a control variabel. The study foccuses on Propery and Real Estate firms listed on the Indonesia Stokc Exchange during the 2017–2023 period. Using purpossive sampling, 13 companies were selected to form the final sample. The data analaysis employed multipel linear regresion, utilizing Eviews software as the primary analytical tool. Based on the evaluation, the Random Efect Model (REM) was identified as the most apropriate model for the dataset. Findings indicate that 25.6% of the fluctuations in stock pricess can be explined by variations in capital structure and dividend policy, alongside the control variable, return on assets. The remmaining 74.4% is influenced by other faktors not considred in this study. Results from the t-test reveal a significant negative relationship betwen capital structure and stocck prices, whereas dividend policy shows a significan positive effect. Additionally, the F-test supports the conclusion that capital structure, dividend policy, and profitability jointly exert a meaningful impact on stock price performance.